Isfram 2014 Proceedings of the International Symposium on Flood Research and Management - Bakar, Sahol Hamid Abu (Springer, 2015)
The world is frequently being devastated by unpredictable disasters. Years of civilization of a nation can simply be shattered by a disaster such as tsunami in a matter of hours. Flooding has been one of the most disastrous natural hazards striking many parts of the world. The increasing trend in flood disasters has resulted from the combined impacts of several factors including global warming effects (e.g., increasing frequency of intense rain, glacier melting, and sea-level rise), landuse changes, and growing population in flood-prone areas...